HADIS SEBAGAI SUMBER HUKUM ISLAM (Studi Metode Komparasi-Konfrontatif Hadis-Al- Qur’an Perspektif Muhammad Al-Ghazali dan Yusuf al-Qaradawi) - Amrulloh, A. (Ahkam: Jurnal Hukum Islam, 2015)
This article discusses the idea of Muhammad al-Ghazali (1917-1996M) in his book, al-Sunnah al-Nabawiyyah bayna Ahl al-Hadith wa Ahlal-Fiqh, and Yusuf al-Qardawi, Kayfa Nata‘amalu ma‘a al-Sunnahal-Nabawiyyah, about comparative and confrontative method indetermining the qualiy of the text of hadith. Regarding the positionof al Quran and Hadith, both scholars employ the same method thatis understanding hadith based on al quran. Yusuf Al Qardawi’ theorywhich is in line the criticism of conventional hadith is devoted tobalance Muhammad al Ghazaly’ theory which is controversial in thedecision of correct hadith. Identifying the similarity and differencesbetween the two scholars is useful in deciding which hadith deservesto be used as source of law after al quran.Kata kunci: Sumber Hukum Islam, Kritik Hadis, Hadis-al-Quran,Muhammad al-Ghazali, Yusuf al-Qaradawi